A baseband circuit for wake-up receivers with double-mode detection and enhanced sensitivity robustness - 朱文锐 杨海钢 高同强 刘飞 程小燕 张丹丹 (Journal of semiconductors, 2013)
This paper proposes a baseband circuit for wake-up receivers with double-mode detection and enhanced sensitivity robustness for use in the electronic toll collection system.A double-mode detection method,including amplitude detection and frequency detection,is proposed to reject interference and reduce false wake-ups.An improved closed-loop band-pass filter and a DC offset cancellation technique are also newly introduced to enhance the sensitivity robustness.The circuit is fabricated in TSMC 0.18μm 3.3 V CMOS technology with an area of 0.12 mm2.Measurement results show that the sensitivity is -54.5 dBm with only a±0.95 dBm variation from the 1.8 to 3.3 V power supply,and that the temperature variation of the sensitivity is±1.4 dBm from -50 to 100℃. The current consumption is 1.4 to 1.7μA under a 1.8 to 3.3 V power supply.